2022
DOI: 10.1108/fs-01-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of big data analytics talent capability on business intelligence infrastructure to achieve firm performance

Abstract: Purpose The emerging attention in big data has led businesses to improve big data analytics talent capability to enrich firm performance. The big data capability pays off for some companies but not for all, and it appears that very few have achieved a big impact through big data. Rooted in the latest literature on the knowledge-based view, IT capability, big data talent capability and business intelligence, this study aims to examine how big data talent capability impact on business intelligence infrastructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Projects based on Big Data are seen as complex and challenging (Rantala et al , 2020). There is also a lack of direction as to how to link Big Data to firm strategy (Ram and Zhang, 2021; Khan et al , 2022) and a lack of suitable talent to exploit data (Qaffas et al , 2022). Of Big Data projects that are started, it is estimated that half are never completed because of lack of skills, technology or market driven requirements (Marr, 2015).…”
Section: Importance Of Understanding the Strategic Benefits Of Big Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Projects based on Big Data are seen as complex and challenging (Rantala et al , 2020). There is also a lack of direction as to how to link Big Data to firm strategy (Ram and Zhang, 2021; Khan et al , 2022) and a lack of suitable talent to exploit data (Qaffas et al , 2022). Of Big Data projects that are started, it is estimated that half are never completed because of lack of skills, technology or market driven requirements (Marr, 2015).…”
Section: Importance Of Understanding the Strategic Benefits Of Big Datamentioning
confidence: 99%
“…As links between data projects and firm strategy are currently lacking, (Ram and Zhang, 2021;Khan et al, 2022), the identification of outcomes will help managers in defining their own project goals and help to connect them to the firm's strategy. In addition, the organization of the outcomes into themes and contexts should help practitioners allocate appropriate human resources to oversee projects, mitigating the impacts of a current lack of talent in this area (Qaffas et al, 2022).…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This managed knowledge will enable the organization to fulfill customer demands quickly and efficiently (Higgins, 2014). A few other studies have shown that in developing a new product, customer requirement is a critical factor (Lassnig et al, 2021;Qaffas et al, 2022).…”
Section: Customer Knowledge Management (Ckm)mentioning
confidence: 99%
“…Technology-enabled leadership (TEL) is a critical link between market environments and business practices, which adopts business analytics in innovative strategic and operational decision-making processes (Kurzhals et al, 2020;Uhl-Bien and Arena, 2018;Wang and Xu, 2019). Business analytics is crucial in defining the paths for competitive capabilities in terms of productivity, agility and value delivery (Aydiner et al, 2019a(Aydiner et al, , 2019bDuan et al, 2020;O'Neill and Brabazon, 2019;Qaffas et al, 2022;Seddon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%